2003
DOI: 10.1136/jnnp.74.8.1085
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment in HTLV-1 infection: a comparative study among TSP/HAM, asymptomatic carriers, and healthy controls

Abstract: Background: Human T cell lymphotropic virus type 1 (HTLV-I) can cause tropical spastic paraparesis/ HTLV-1 associated myelopathy (TSP/HAM) and adult T cell leukaemia/lymphoma. More recently other diseases such as isolated peripheral polyneuropathy, myopathy, artropathy, and uveitis have been associated with this retrovirus. Only a few uncontrolled studies, without necessary exclusion criteria, have described mild cognitive deficits among TSP/HAM patients. To further clarify this the authors evaluated, through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 26 publications
1
30
1
1
Order By: Relevance
“…Most of the published papers about cognitive disturbances in HAM/TsP describe psychomotor slowing, attention deficits as well as visual and working memory deficits 16,17 . In the only controlled study using an extensive neuropsychological battery, HTLV-1 infection was associated with mild cognitive deficits characterized by impairments in psychomotor speed, verbal fluency, verbal and visual memory, selective and alternate attention (flexibility), and visuoconstructive abilities 18 .…”
Section: Encephalopathy and Cognitive Deficitsmentioning
confidence: 99%
“…Most of the published papers about cognitive disturbances in HAM/TsP describe psychomotor slowing, attention deficits as well as visual and working memory deficits 16,17 . In the only controlled study using an extensive neuropsychological battery, HTLV-1 infection was associated with mild cognitive deficits characterized by impairments in psychomotor speed, verbal fluency, verbal and visual memory, selective and alternate attention (flexibility), and visuoconstructive abilities 18 .…”
Section: Encephalopathy and Cognitive Deficitsmentioning
confidence: 99%
“…These symptoms and conditions may later progress to HAM or constitute isolated neurologic syndromes associated with HTLV infection. Sensory neuropathy, [6][7][8] gait abnormalities, 9,10 bladder dysfunction, 6,9-12 erectile dysfunction, 13,14 ALS, 15 mild cognitive deficits, 16 and rarely, motor neuropathies 6,8,13,[17][18][19] have all been reported among HTLV-I-infected individuals without HAM. Although less research has focused on HTLV-II, sensory neuropathy has been observed with HTLV-II alone 20 and with HIV coinfection.…”
mentioning
confidence: 99%
“…Besides the CMCT measurements discussed above, more sophisticated and sensitive TMS measures that detect early changes in thalamocortical-basal ganglia circuitry 20,83,84 such as cortical thresholds, recruitment curves, silent periods, and excitatory and inhibitory phenomena produced by short and long interval stimulation obtained by single and paired magnetic stimulation are worth trying in HIV asymptomatic patients as well as in HTLV-I carriers at times when the fastest corticospinal fibers remain uninvolved 11,12,24,76,[85][86][87][88][89] . This can be done in order to better understand cortico-cortical and neurotransmitter dysfunction early in disease development 90 , and it will also allow the application of more appropriate and effective neuromodulatory measures long before the fatal clinical AIDS or HAM/TSP appears.…”
Section: Discussionmentioning
confidence: 99%